2008
DOI: 10.1002/ps.1644
|View full text |Cite
|
Sign up to set email alerts
|

Phytotoxicity of GF‐120® NF Naturalyte® fruit fly bait carrier on sweet cherry (Prunus avium L.) foliage

Abstract: Applying GF-120 to the adaxial leaf surface, or at doses of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Spinosad formulations with bait (Spintor ® ) have proved to be as effective as malathion, but some fruit damage problems were described in 2004 and 2005 in citrus and in other crops when Spintor ® was applied in spots (Alfaro F, private communication). In fact, scars appear at the point where the bait spot touches the fruit or the leaves …”
Section: Introductionmentioning
confidence: 99%
“…Spinosad formulations with bait (Spintor ® ) have proved to be as effective as malathion, but some fruit damage problems were described in 2004 and 2005 in citrus and in other crops when Spintor ® was applied in spots (Alfaro F, private communication). In fact, scars appear at the point where the bait spot touches the fruit or the leaves …”
Section: Introductionmentioning
confidence: 99%
“…Factors such as rainfall (Piñero et al 2009a) and phytotoxicity (DeLury et al 2009) may influence the efficacy or utility of foliar applications of insecticidal baits. In a previous study (Piñero et al 2009a) rainfall that fell during or shortly after foliar applications of GF-120 in commercial papaya, Carica papaya L. (Brassicales: Caricaceae), orchards reduced bait effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…Intensive research has demonstrated that PLMs not only protect GF-120 against rainfall but also enhance the behavioral response of adult fruit flies to this bait and extend its attractiveness for at least one week (Piñero et al 2009b). Furthermore, the application of insecticidal baits onto PLMs circumvents the phytotoxicity caused by this bait on some crops (DeLury et al 2009) and minimizes degradation of spinosad by photolysis (Mangan et al 2006). …”
Section: Introductionmentioning
confidence: 99%
“…However, spinosad formulations with bait (Spintor ® ) have only shown an efficacy equal to that of malathion 2. Moreover, some foliage damage3 and citrus fruit scars (Alfaro F, private communication) have been described when Spintor ® was applied in spots. Actually, scars appeared at the point where the bait spot touched the fruit.…”
Section: Introductionmentioning
confidence: 99%